119 Antihypertensive deprescribing in long-term care: a randomized controlled trial (OptimizeBP). (8th June 2022) - Kraut, Roni; Sadowski, Cheryl; Youngson, Erik; Faulder, Douglas; Korownyk, Christina; Bakal, Jeff; Garrison, Scott
Abstract : Objective: Although antihypertensive medication use is common in frail older adults, observational evidence and expert opinion suggest that, in this population, blood pressure lowering may have limited benefit and could even be harmful. A randomized controlled trial of antihypertensive deprescribing that examines clinical outcomes in this population is needed. The objective is to determine whether deprescribing antihypertensive medication to a systolic blood pressure of 140 ±5 mmHg, compared to standard practice, will reduce mortality in frail older adults in long-term care facilities. Method: Design: Randomized controlled, 2 parallel groups, open-label, event-driven trial, ending upon observation of 247 primary outcomes. The trial is supported by the Alberta SPOR SUPPORT Unit Data and Research Services Team, a governmental steward of Alberta administrative health claims data, who will 1) use Alberta Health Services administrative claims data to identify eligible residents; 2) randomize those residents centrally to intervention or control; and 3) track and analyze all study outcomes. Participants: Hypertensive long-term care residents ≥70 years of age in the province of Alberta, Canada, with mean systolic blood pressure <135 mmHg and taking ≥1 daily antihypertensive medication. Intervention: Facility pharmacists will deprescribe antihypertensive medication every second week, targeting a systolic blood pressure of 140 ±5 mmHg using an algorithm developed by investigators and reviewed by pharmacists, geriatricians, and the Cochrane Hypertension Working Group. Outcome measures: All-cause mortality (primary outcome), quality of life, and cost. Results: The pilot stage of this trial was completed in a 200-bed long-term care facility in fall 2021. Of the eleven residents eligible for deprescribing during the pilot, 5 had all antihypertensives discontinued, and the remaining 6 discontinued or dose-reduced ≥50% of antihypertensives. The subsequent three participating facilities had all eligible residents randomized in April 2022. Randomization of residents at several other long-term care facilities is anticipated by fall 2022, with final results expected in 2024. Conclusion: Deprescribing antihypertensive medication in long-term care residents is feasible, based on the pilot phase of our trial. The full trial will provide evidence on the benefits and potential risks of antihypertensive deprescribing in a frail older adult population.